2004
DOI: 10.1073/pnas.0406048101
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of repair processes for oxidative DNA damage in mammalian cells

Abstract: Oxidative DNA damage causes blocks and errors in transcription and replication, leading to cell death and genomic instability. Although repair mechanisms of the damage have been extensively analyzed in vitro, the actual in vivo repair processes remain largely unknown. Here, by irradiation with an UVA laser through a microscope lens, we have conditionally produced single-strand breaks and oxidative base damage at restricted nuclear regions of mammalian cells. We showed, in real time after irradiation by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
298
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(344 citation statements)
references
References 31 publications
41
298
3
2
Order By: Relevance
“…While PARP1 depletion does not affect PCNA recruitment, as shown previously [34,36,53], it decreases PARG recruitment to DNA damage sites [36,37]. Using simultaneous dual-channel imaging we showed that in the absence of PARP1, PARG and PCNA are recruited with a comparable kinetic mechanism at a single cell level.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…While PARP1 depletion does not affect PCNA recruitment, as shown previously [34,36,53], it decreases PARG recruitment to DNA damage sites [36,37]. Using simultaneous dual-channel imaging we showed that in the absence of PARP1, PARG and PCNA are recruited with a comparable kinetic mechanism at a single cell level.…”
Section: Discussionsupporting
confidence: 80%
“…Both laser settings induced fast and transient recruitment of PARP1, coupled with transient accumulation of PAR, in contrast to sustained accumulation of γH2AX, which persisted > 30 min after irradiation (Figure 1). While PARP1 recruitment and PAR production may be used as a marker of both SSBs and DSBs [29,34], phosphorylation of the histone variant H2AX (γH2AX) is primarily induced at DSBs and is known to spread megabases away from the damage site and persist beyond the time required for DSB repair [45,46]. Given that PAR and γH2AX do not exhibit the same distribution along the laser stripe (Figure 1, bottom overlay panels), both SSBs and DSBs seem to be formed under our experimental conditions.
10.1080/19491034.2018.1516485-F0001Figure 1. DNA damage induction with a UV-A 355 nm laser coupled with BrdU presensitization .
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of techniques have been developed to fulfill this purpose, however, all these methods require laser sources or other specific devices. For example, a study using an ultraviolet A (UVA) laser in combination with BrdU-labelling stimulated experiments using UVA lasers of different wavelengths to examine the spaciotemporal dynamics of the factors involved in DNA damage response and DNA damage repair (8)(9)(10)(11)(12)(13)(14). More recently, green and near-infrared lasers, which do not require BrdU-labelling, have been applied (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%